The journal Communications in Numerical Methods in Engineering with Biomedical Applications becomes the International Journal for Numerical Methods in Biomedical Engineering (IJNMBE) from 1st January 2010 - Nithiarasu, Perumal; Löhner, Rainald (International journal for numerical and analytical methods in geomechanics, 2009)
Communications in Numerical Methods in Engineering, founded by Roland W. Lewis in 1985, will change its title to the ‘International Journal for Numerical Methods in Biomedical Engineering’ and has a revised Aims and Scope. Copyright © 2009 John Wiley & Sons, Ltd.